Correction: pH sensitive water-in-water emulsions based on the pullulan and poly(,-dimethylacrylamide) aqueous two-phase system - Plucinski, Alexander; Schmidt, Bernhard V. K. J (Polymer chemistry, 2022)
Correction for 'pH sensitive water-in-water emulsions based on the pullulan and poly( N , N -dimethylacrylamide) aqueous two-phase system' by Alexander Plucinski and Bernhard V. K. J. Schmidt, Polym. Chem. , 2022, https://doi.org/10.1039/d2py00469k .